Pengelolaan Dokumentasi Kegiatan Humas pada Institusi di Balai Diklat Lingkungan Hidup dan Kehutanan Kota Pekanbaru - Johan Faladhin; Ulmi Marsya; M Tazri (Lembaga penelitian dan pengabdian kepada masyrakat, 2020)
The importance of environmental awareness must receive a special attention from public especially in Pekanbaru which is often affected by environmental demage such as wildfire or illegal logging. The existence of Balai Diklat Lingkungan dan Kehutanan (BDLHK) of Pekanbaru is expected to be able to provide the valid and educative information about environmental issues. Refers to those issues, they need to improve their abiltity to manage institusion’s company profile, informnation management through social media platform, and creating educative, creative, and persuasive content in stop motion video. The purpose of using social media platform is to achieve the society especially youth generation. There are three outputs of this event. first, basic training of making intitusion company profile, second, stop motion video, third, do the social campaign through social media. Hopefully the contribution of this program will be sustainable going forward.